How Social Media Marketing and Online Customer Reviews Shape Purchase Decisions: The Role of Brand Awareness - Ardik Praharjo; Naila Erliyan; Noor Aziz (Global Review of Tourism and Social Sciences, 2025)
This research aims to analyze the influence of social media marketing and online customer reviews on purchase decisions via Instagram Reels, with brand awareness as a mediating variable. The research adopts a quantitative approach with a population of Pinkflash Instagram followers who have previously purchased its products. The number of samples used in this research was 100 respondents using techniques purposive sampling. Data was collected using an online questionnaire. The data analysis method used is a range of scales and Structural Equation Model (SEM) with software SmartPLS 4.0. The results indicate that brand awareness significantly influences purchase decisions. Online customer reviews have a significant positive influence on brand awareness but do not directly impact purchase decisions. Social media marketing positively influences both brand awareness and purchase decisions. Furthermore, both online customer reviews and social media marketing have indirect positive effects on purchase decisions through brand awareness.